Magmatic Evolution and Plumbing System of Gede-Salak Volcano, Banten, Indonesia - Muhammad Alfath Salvano Salni; Euis Tintin Yuningsih; Tsukasa Ohba (Geological Agency, 2023)
The study of individual volcanoes in northwest Java has been largely overlooked. In this study, an investigation of the magma evolution and plumbing system of Gede-Salak Volcano was conducted. A geological survey determined the lava unit and volcanism. The whole-rock geochemistry is utilized to determine the magma type and evolution. Mineral chemistry based on microprobe analysis revealed the magmatic process and phenocryst origin. Geothermobarometry is employed to estimate the temperature and pressure. The volcanism comprised the eruption of lava flows, sector collapse, and the eruption of lava domes. The magma evolution consists of two magma types: type A (lava flow and peripheral dome) and type B (summit dome). The processes identified are amphibole fractionation, magma mixing, and crust assimilation. Phenocryst textures and chemistry implied open-system processes inthe plumbing system involving three magma series, namely the felsic, intermediate, and mafic series. Magma type A resulted from multiple mafic recharges on the felsic series, while type B resulted from the mixing of intermediate and mafic series. The felsic and intermediate phenocryst crystallization occurred at 933-948°C and 1010-1011°C in the mid-crust at 14 km to 17 km depth. Meanwhile, the mafic series reside in the lower crust at 21 km depth and of 1065-1087°C temperature. Keywords: Gede-Salak, magma evolution, magma plumbing, geothermobarometry, mineral chemistry